2021
DOI: 10.3389/fpsyt.2021.679960
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parvalbumin Interneurons in Neurotransmitter Balance and Neurological Disease

Abstract: While great progress has been made in the understanding of neurological illnesses, the pathologies, and etiologies that give rise to these diseases still remain an enigma, thus, also making treatments for them more challenging. For effective and individualized treatment, it is beneficial to identify the underlying mechanisms that govern the associated cognitive and behavioral processes that go awry in neurological disorders. Parvalbumin fast-spiking interneurons (Pv-FSI) are GABAergic cells that are only a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 93 publications
(146 reference statements)
0
39
0
Order By: Relevance
“…GABAergic PV interneurons constitute around 30%–50% of the total number of inhibitory cells in the neocortex and participate in the control and regulation of cortical networks through local regulation and stabilization of excitatory activity (Batista‐Brito et al, 2020). Thus, PV interneurons contribute to overall excitatory/inhibitory balance (Nahar et al, 2021) which impacts learning and memory behaviors (Murray et al, 2015). Moreover, these neurons regulate neural synchrony within microcircuits (Ruden et al, 2021) and, thus, potentially contribute to functional connectivity deficits observed using resting‐state MRI following AIE exposure (Broadwater et al, 2018; Gómez‐A et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…GABAergic PV interneurons constitute around 30%–50% of the total number of inhibitory cells in the neocortex and participate in the control and regulation of cortical networks through local regulation and stabilization of excitatory activity (Batista‐Brito et al, 2020). Thus, PV interneurons contribute to overall excitatory/inhibitory balance (Nahar et al, 2021) which impacts learning and memory behaviors (Murray et al, 2015). Moreover, these neurons regulate neural synchrony within microcircuits (Ruden et al, 2021) and, thus, potentially contribute to functional connectivity deficits observed using resting‐state MRI following AIE exposure (Broadwater et al, 2018; Gómez‐A et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In some cortical areas, PVALB+ interneurons make up to 50% of the interneuronal population and target up to 200 pyramidal cells per single cell. Even small changes in interneuronal numbers or functionality can interfere with the proper orchestra of neuronal function in distinct cortical areas [ 25 , 58 , 59 ]. Impairments of GABAergic interneurons have been related to preterm birth brain injury and oxidative stress (OS).…”
Section: Discussionmentioning
confidence: 99%
“…PV-positive cells can be found in different brain regions, contributing significantly to information processing in a variety of brain circuits [36]. In the neocortex and hippocampus, PV neurons have been confirmed to have functional autapses; similar to certain types of conventional synapses, these autapses possess two modes of neurotransmitter release, synchronous and asynchronous mode [17,19,37]. Recordings from acute cortical slices revealed that the percentage of autaptic PV cells in rodent (~85%) is more than that found in human (64.3%) [17,19].…”
Section: Discussionmentioning
confidence: 99%